Impact Of A Credit Course On Value Education For Consciousness Development On The Happiness Relationships And Self Discipline Of The Students In Atmiya University - Kalariya Ankit Kumar Keshavlal; Patel Jaykumar Ashwinbhai (Educational Administration: Theory and Practice, 2024)
Credit course on Value Education for Consciousness Development (VECD) has been running across many universities of the country for the past few years. The course discusses issues which are very basic, sensitive and prime requirements nowadays are to be happy, relationships and self discipline of students. The content is shared in the form of a proposal for self-verification, self-validation by the students. Students reflect on the content on the basis of their natural acceptance and also validate it in their living by experiments. The complete content of the course has been designed in a way so that it is universal, logical, verifiable and leading to harmony with self, family, society and nature. In 2019, Atmiya University in Rajkot, Gujarat, India started running such a full-semester three-credit course. After the completion of the course, a survey was conducted on approx 1372 students to evaluate their happiness, relationship and self-discipline of the students. One of the survey results and their analysis is discussed in this paper. The survey suggests that this course has been transformational in terms of initiating a process of self-exploration and self-reflective thinking on happiness, self-discipline and relationship in the students. The students develop a holistic perspective of life, an understanding of the need for physical facilities in life, the underlying feelings for harmonious relationships, co-existence of human order with the nature around them, and are able to overcome negative emotions through this course within a short span of time. It also suggests that values can be inculcated among the scholars of higher education through classroom inputs if the pedagogy includes exploration techniques, open discussion and creative individual and group level practice sessions. These outcomes suggest immense possibilities for higher education – starting with value education to value-based education leading to value-based living.